2016
DOI: 10.1038/srep18528
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine levels contribute to the pathogenesis of minimal hepatic encephalopathy in patients with hepatocellular carcinoma via STAT3 activation

Abstract: Hepatocellular carcinoma (HCC) patients were grouped according to the degree of encephalopathy, with healthy volunteers as controls. We investigated clinical presentation, protein and mRNA expression of 14 cytokines, and activation of six STAT proteins, the downstream signaling mediators. Levels of all 14 cytokines were significantly elevated in HCC patients with clinical hepatic encephalopathy. Statistical analysis showed that levels of IL-1β, IL-6, IFNγ, IL-17α, IFNλ2 and IFNλ3 were correlated with minimal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
(46 reference statements)
0
14
1
Order By: Relevance
“…IL‐6 released from T cells can induce proliferation and differentiation of B cells, as well as stimulate antibody production. Recent studies have revealed that the expression of IL‐6 in primary liver cancer was dramatically elevated and is positively correlated with morbidity and progression . IL‐6 exerts its biological effects through binding to two subunits of signal transducing receptor GP130 and IL‐6R, resulting in dimerization of GP130 and IL‐6R and subsequently activation of the Janus kinases/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL‐6 released from T cells can induce proliferation and differentiation of B cells, as well as stimulate antibody production. Recent studies have revealed that the expression of IL‐6 in primary liver cancer was dramatically elevated and is positively correlated with morbidity and progression . IL‐6 exerts its biological effects through binding to two subunits of signal transducing receptor GP130 and IL‐6R, resulting in dimerization of GP130 and IL‐6R and subsequently activation of the Janus kinases/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, activated STAT3 is necessary not only for oncogenesis and tumor progression, but also for invasion of HCC in vitro and in vivo . Levels of cytokines were found to be elevated in HCC, especially IL‐6 . IL‐6 binds to IL‐6R to form a binary complex and further combines with GP130 to transduce extracellular signaling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an evidence about the role of cytokines in the progression of HCC. 16 In response to infections and inflammation caused by hepatitis viruses (HBV and HCV), the inflammatory cells secrete cytokines and chemokines, which contribute to the liver damage and progression of HCC. The cytokines that were shown to be involved in the hepatocarcinogenesis are IL-1 b, IL-2, IL-1b, IFN-g, TNF-a, IL-4, IL-10, IL-6, and TGFB.…”
Section: Cytokines and Chemokines As Factorsmentioning
confidence: 99%
“…56 B generally exerts anticancer action either by triggering the mitochondrial pathway of apoptosis or by inducing cellular stress, such as cytokine withdrawal and DNA damage. [7][8][9][10][11][12][13][14][15][16][17][18] Thus, we investigated the altered levels of cytokines and caspases among different groups through ELISA and screened the effects of B and BNP treatments over the carcinogen control group.…”
mentioning
confidence: 99%